2018
DOI: 10.1016/j.ebiom.2018.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Defining Bedaquiline Susceptibility, Resistance, Cross-Resistance and Associated Genetic Determinants: A Retrospective Cohort Study

Abstract: BackgroundBedaquiline (BDQ) is a novel agent approved for use in combination treatment of multi-drug resistant tuberculosis (MDR-TB). We sought to determine BDQ epidemiological cut-off values (ECVs), define and assess interpretive criteria against putative resistance associated variants (RAVs), microbiological outcomes and cross resistance with clofazimine (CFZ).MethodsA retrospective cohort study was conducted. Minimal inhibitory concentrations (MIC) to BDQ were determined using 7H9 broth microdilution (BMD) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
109
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 107 publications
(121 citation statements)
references
References 32 publications
11
109
0
1
Order By: Relevance
“…In this study, we show that the increase of MIC to bedaquiline and clofazimine could be explained by mutations emerging during therapy in Rv0678 . As reported in table 1 we observed four different mutations and three of these (138-139_Ins-G, 141-142_Ins-C, 192-193_Ins-G) were previously reported as associated to bedaquiline resistance in MTB clinical strains (8). We show that the same mutations are associated to Clofazimine resistance.…”
Section: Manuscriptsupporting
confidence: 69%
See 1 more Smart Citation
“…In this study, we show that the increase of MIC to bedaquiline and clofazimine could be explained by mutations emerging during therapy in Rv0678 . As reported in table 1 we observed four different mutations and three of these (138-139_Ins-G, 141-142_Ins-C, 192-193_Ins-G) were previously reported as associated to bedaquiline resistance in MTB clinical strains (8). We show that the same mutations are associated to Clofazimine resistance.…”
Section: Manuscriptsupporting
confidence: 69%
“…The genetic basis of resistance to bedaquiline is still the subject of much uncertainty. WGS analysis in different studies showed that bedaquiline-clofazimine cross resistance arises through mutations in Rv0678 (6,7,8) and pepQ (9). In this study, we show that the increase of MIC to bedaquiline and clofazimine could be explained by mutations emerging during therapy in Rv0678 .…”
Section: Manuscriptmentioning
confidence: 99%
“…Characterized RAVs include mutations in BDQ target gene atpE (3), efflux pump regulator gene Rv0678 (8)(9)(10), gene pepQ (11,12), and gene Rv1979c (12). atpE RAVs that reduce BDQ activity have been observed previously in vitro (13) but rarely in patient clinical isolates (14,15). In contrast, mutations in Rv0678 have led to low-level resistance in isolates obtained both in vitro and in the clinic (15).…”
mentioning
confidence: 99%
“…As such, it exerts strong selection pressure and bactericidal and sterilizing companion drugs are necessary to restrict the selective amplification of spontaneous BDQ-resistant mutants. Previous studies have identified BDQ-resistant mutants selected in vitro , in mice and in TB patients (13, 2931). In most cases in which it emerged in vivo , resistance was attributable to mutations in the transcriptional repressor Rv0678 or in the predicted proline aminopeptidase pepQ , although the latter mutation target has yet to be confirmed in BDQ-resistant clinical isolates.…”
Section: Discussionmentioning
confidence: 99%